2006
DOI: 10.1002/eej.20286
|View full text |Cite
|
Sign up to set email alerts
|

Technologies and applications of Al‐free high‐power laser diodes

Abstract: TSUYOSHI OHGOH, TOSHIAKI FUKUNAGA, and TOSHIRO HAYAKAWA Frontier Core-Technology Laboratories, R&D Management Headquarters, Fuji Photo Film Co., Japan SUMMARYWe report high-power technologies in 0.8-µm Al-free InGaAsP/InGaP laser diodes. To realize the high-power operation, the improvement of catastrophic optical mirror damage (COMD) power density level is required. In addition to the use of low surface recombination velocity of Al-free materials, optimization of waveguide thickness in broad waveguide structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The same group also reported facet temperature analysis in quantum cascade devices [123,129]. Hayakawa et al [120][121][122] investigated the impact of device design parameters such as emitter stripe width and waveguide thickness on the facet temperature. Piva et al [57,58] quantified the effect of QW intermixing to facet temperatures and found a substantially reduced facet temperature for devices with non-absorbing mirrors.…”
Section: Reflectance Modulation and Thermoreflectancementioning
confidence: 99%
See 1 more Smart Citation
“…The same group also reported facet temperature analysis in quantum cascade devices [123,129]. Hayakawa et al [120][121][122] investigated the impact of device design parameters such as emitter stripe width and waveguide thickness on the facet temperature. Piva et al [57,58] quantified the effect of QW intermixing to facet temperatures and found a substantially reduced facet temperature for devices with non-absorbing mirrors.…”
Section: Reflectance Modulation and Thermoreflectancementioning
confidence: 99%
“…The required lateral resolution is achieved with a microscope and lock-in detection schemes result in high detection sensitivities. The required reflectance modulation is typically achieved by temperature modulation of the investigated device via the operation current [28,39,57,58,117,118,[120][121][122]. In contrast to the micro-Raman-approach, one records only two scalar quantities, namely R and ΔR at the particular wavelength (typically via two channels of the look-in amplifier)…”
Section: Reflectance Modulation and Thermoreflectancementioning
confidence: 99%
“…Other papers have studied the influence of unpumped windows on laser diode reliability, either by simulation [4] or experimentally [3], [11]. In [11], Ohgog and al studied the effect of a current blocking region on the light output power and on the driving current. In [3], Rinner uses μ-Raman spectroscopy to evaluate the facet and averaged waveguide temperatures.…”
Section: Temperature Variation Measurementsmentioning
confidence: 99%
“…14 Although the quality of facet mirror passivation was greatly improved and AlGaAs-based diode lasers later proved their reliability, Al-free laser heterostructures still remain an alternative solution for high-power diode lasers (see, e.g., Refs. 13,15,and 16).…”
Section: Introductionmentioning
confidence: 99%